Pengembangan Profesi Guru Sebagai Upaya Meningkatkan Kualitas Peserta Didik Kelas Religi di SMPN 2 Kota Bengkulu - Sutra, Deni (GHAITSA : Islamic Education Journal, 2021)
This research was designed with the aim of improving the quality and activeness of students' learning by using a group discussion learning model and individual memorization for students at SMP N 02 Bengkulu City in the Religious class. The research method used was the classroom action method (PTK) which was carried out at Junior high school/ SMP N 02 Bengkulu City. The research objects are Religious Class students for the 2023-2024 academic year, namely Religious Program students in grades seven, eight and nine. The religious program in class K is a special class for students who are involved in religion. This class is a class specifically for training oneself to memorize the Al-Qur'an properly and correctly so as to produce students with noble character and memorizing the Al-Qur'an. The research plan is classroom action research. This research was carried out over two actions (cycles). Each action includes planning, implementation, observation and reflection. Data collection techniques through learning outcomes tests in memorizing the Al-Qur'an for students. The research object is the Qur'an tahfidz teacher and the students' active learning